(untitled) (Neo Scientific Peer Reviewed Journal, 2023)
In this article, the history of the study of eimeria in rabbits and the scientific research works of scientists who have been active in the promotion of this disease have been analyzed, focusing on some of the oocysts that cause the disease, giving detailed information about them.